Cinnamon as a Useful Preventive Substance for the Care of Human and Plant Health - Jolanta Kowalska; Józef Tyburski; Kinga Matysiak; Magdalena Jakubowska; Joanna Łukaszyk; Joanna Krzymińska (Molecules, 2021)
Cinnamon is widely used as a food spice, but due to its antibacterial and pharmacological properties, it can also be used in processing, medicine and agriculture. The word “Cinnamon” can refer to the plant, processed material, or an extract. It is sometimes used as a substance, and sometimes used as a mixture or as compounds or a group. This article reviews research into the effectiveness of various forms of cinnamon for the control of plant diseases and pests in crops and during storage of fruit and vegetables. Cinnamon acts on pests mainly as a repellent, although in higher doses it has a biocidal effect and prevents egg-laying. Cinnamon and its compounds effectively hinder bacterial and fungal growth, and the phytotoxic effects of cinnamon make it a possible herbicide. This article presents the wide practical use of cinnamon for various purposes, mainly in agriculture. Cinnamon is a candidate for approval as a basic substance with protective potential. In particular, it can be used in organic farming as a promising alternative to chemical pesticides for use in plant protection, especially in preventive treatments. The use of natural products is in line with the restriction of the use of chemical pesticides and the principles of the EU’s Green Deal.